Kointegrasi antara Profitabilitas, Solvabilitas dan Kapitalisasi Pasar - Ika Yoga; Rais Sani Muharrami (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2016)
This research aims to uncover long-term relationship (cointegration) between market capiltalization, profitability and solvability on the companies which listed in the Jakarta Islamic Index (JII) in the period 2011-2014 using secondary data from website BEI and Indonesian Capital Market Directory (ICMD). The method of this study using Johansen Cointegration Test, the result of this research show that there are cointegration between profitability and solvability to market capitalization.